Pratiques linguistiques et durabilité. Quel est le rôle d'une langue minoritaire dans le développement local ? - Katherine Cortés Montoya (Lengas)
This contribution will examine the relationship between linguistic practices and the development of the indigenous Misak community in Colombia. Based on qualitative data from two field surveys conducted in the Guambía resguardo, Cauca department, in 2021 and 2022, our approach includes semi-structured interviews, participant observations, and workshops in the indigenous language (TERPLO) with students at various levels. Our theoretical framework will be grounded in the principles of Giovanni Agresti's Social Development Linguistics, which emphasizes on-the-ground intervention in collaboration with language speakers to improve the quality of life for marginalized populations. By analyzing the Misak case, we will identify the crucial role of minority languages in the intergenerational transmission of ancestral knowledge and community practices, thereby promoting sustainable development and territorial reappropriation.